Congenitally corrected transposition with absent pulmonary valve: Hitherto unreported association. Issue 7 (12th April 2022) - Sharma, Arun; Naganur, Sanjeev Hanumantacharya; Baranwal, Arun Kumar; Singhal, Manphool
Abstract: Absent pulmonary valve has usually been described in association with tetralogy of Fallot. Present case highlights its association with congenitally corrected transposition which has not been reported so far in literature.